Temperature-sensitive water-responsive shape memory effect in plant leaves - Wang, Tao Xi (2022)
Some plants have been reported to have the water-induced shape memory effect (SME). Since the tissue system of most plant leaves is a biophysical sandwich-like structure composed of epidermis, mesophyll and veins, the leaves are actually bio-composites. In this paper, we experimentally investigated the contribution of different tissues to the SME in dried plant leaves (namely, soursop, sugar apple, and longan) and skeleton (i.e., cuticle and lamina removed) leaves (soursop only). Shape recovery in the leave strips, and skeleton soursop leave strips, all programmed (deformed) via rolling and drying, was activated by room temperature water, hot (90 °C) water, or pure heating (up to 230 °C) to uncover the influence of temperature in the SME. Although heating alone does not induce any apparent shape recovery, hot water causes much faster recovery than room temperature water. Besides, same as the influence of the maximum programming strain on the heating-responsive shape recovery in shape memory polymers, less programmed leaves (i.e., with smaller maximum programming strain) tend to recover faster. Together with other tests (including drying, wetting, drying/wetting, cyclic differential scanning calorimetry, etc.), the contributions/roles of different tissues on the phenomena observed in this study are revealed.